A reflection on mobility and social interactions in places of transport in times of Covid-19: The case of the “Metropolitano”, Lima – Perú - Chavez Leonardo, Aroldo Kevin (2020)
The current Covid-19 pandemic has had an impact on the way we interact in various spaces of our social life, one of these spaces is the large transport stations in many cities in the world. In this sense, for the development of this text, a rapid transit bus system that operates in the city of Lima, the “Metropolitan”, will be an empirical case to reflect on this impact. In this way, to understand said repercussion, in the first place, it will focus on the mobility and social interactions of the users of the Metropolitano until before the pandemic. To do so later, analyze how the present context has impacted on the way of interacting in this transport system. In short, to generate greater support for this text, some responses that have been compiled through a virtual form on the experience of traveling in the Metropolitan in this pandemic will be used and analyzed. Likewise, some ethnographic scenarios that have been recorded, through participant observation, in the Metropolitano stations will be described and analyzed.